2021
DOI: 10.1515/pp-2020-0148
|View full text |Cite
|
Sign up to set email alerts
|

Current practice and perceptions of safety protocols for the use of intraperitoneal chemotherapy in the operating room: results of the IP-OR international survey

Abstract: Objectives To assess the risk perception and the uptake of measures preventing environment-related risks in the operating room (OR) during hyperthermic intraperitoneal chemotherapy (HIPEC) and pressurized intraperitoneal aerosol chemotherapy (PIPAC). Methods A multicentric, international survey among OR teams in high-volume HIPEC and PIPAC centers: Surgeons (Surg), Scrub nurses (ScrubN), Anesthesiologists (Anest), Anesthesiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Several studies examined gloves, hands, devices, injectors, trocars, and floor wiping samples for platin traces and reported highly variable contamination levels [ 6 , 8 , 9 ]. Differences in current practices regarding the PPE required for performing PIPAC have been observed among expert centers [ 18 ]. In this Delphi study, there was a large consensus for the PPE needed to perform PIPAC safely.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies examined gloves, hands, devices, injectors, trocars, and floor wiping samples for platin traces and reported highly variable contamination levels [ 6 , 8 , 9 ]. Differences in current practices regarding the PPE required for performing PIPAC have been observed among expert centers [ 18 ]. In this Delphi study, there was a large consensus for the PPE needed to perform PIPAC safely.…”
Section: Resultsmentioning
confidence: 99%
“…Availability of emergency kits in case of accidental exposure was unknown for 50% of responders. Most OR team members seek supplementary information about the risks related to CA administration [ 18 ]. Another recent study demonstrated that nonmedical caregivers in the OR are aware of the occupational hazards related to the use of CA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to our knowledge, no study measured the platinum concentration in both blood and urine samples. Moreover, despite this encouraging preliminary evidence and the rigorous safety protocol put in place for the medical (Alyami et al, 2020) and non-medical staff (Al Hosni et al, 2020), the use of PIPAC, and also of other types of intraperitoneal chemotherapy procedures, such as hyperthermic intraperitoneal chemotherapy, is still considered as an occupational hazard and requires continuous updating and education (Al Hosni et al, 2020;Clerc D et al, 2021).…”
Section: Introductionmentioning
confidence: 99%